IMPLEMENTATION OF PRACTICAL LIFE SKILL ACTIVITIES TO INCREASE THE INDEPENDENCE OF 3–4 YEAR OLD CHILDREN: AN OBSERVATIONAL STUDY AT THE ANGGREK KINDERGARTEN - Agustiarini Eka Dheasari; Nur Hasanah; Umi Atiyah; Siti Khomsah Apsari (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to describe the implementation of Practical Life Skill activities in increasing the independence of children aged 3-4 years at KB Anggrek Tegalsono. The study used a descriptive qualitative approach with 17 children as research subjects in October 2025. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that Practical Life Skill activities implemented in the learning routine had a positive influence on the development of children's independence. Most children showed development in the Starting to Develop (MB) and Developing According to Expectations (BSH) categories, especially in the ability to put on shoes, tidy up toys, pour water, and clean up the table after the activity. Consistent habituation factors and gradual teacher guidance play an important role in encouraging children to be independent. Thus, Practical Life Skill activities are effectively implemented as a learning strategy to foster independence in early childhood, with ongoing support from teachers and parents.